Measuring the Exercise Component of Energy Availability during Arduous Training in Women. Issue 4 (April 2021) - Gifford, Robert M.; Greeves, Julie P.; Wardle, Sophie L.; O'Leary, Thomas J.; Double, Rebecca L.; Venables, Michelle; Boos, Christopher; Langford, Joss; Woods, David R.; Reynolds, Rebecca M.
ABSTRACT: Introduction: Low energy availability (EA) may impede adaptation to exercise, suppressing reproductive function and bone turnover. Exercise energy expenditure (EEE) measurements lack definition and consistency. This study aimed to compare EA measured from moderate and vigorous physical activity from accelerometry (EEEmpva ) with EA from total physical activity (EEEtpa ) from doubly labeled water in women. The secondary aim was to determine the relationship of EA with physical fitness, body composition by dual-energy x-ray absorptiometry, heart rate variability (HRV), and eating behavior (Brief Eating Disorder in Athletes Questionnaire [BEDA-Q]). Methods: This was a prospective, repeated-measures study, assessing EA measures and training adaptation during 11-month basic military training. Forty-seven women (23.9 ± 2.6 yr) completed three consecutive 10-d assessments of EEEmvpa, EEEtpa, and energy intake (EI). EA measures were compared using linear regression and Bland–Altman analyses; relationships of EA with fat mass, HRV, 1.5-mile run times, and BEDA-Q were evaluated using partial correlations. Results: EA from EEEmvpa demonstrated strong agreement with EA from EEEtpa across the measurement range ( R 2 = 0.76, r = 0.87, P < 0.001) and was higher by 10 kcal·kg −1 FFM·d −1 . However, EA was low in absolute terms because of underreported EI. Higher EA was associated with improved 1.5-mile run time ( r = 0.28, P < 0.001), fat mass loss ( r = 0.38, P < 0.001), and lower BEDA-Q score ( r = −0.37, P < 0.001) but not HRV (all P > 0.10). Conclusion: Accelerometry-based EEE demonstrated validity against doubly labeled water during multistressor training, the difference representing 10 kcal·kg −1 FFM·d −1 EEE from nonexercise activity. Beneficial physical but not autonomic adaptations were associated with higher EA. EAmvpa and BEDA-Q warrant consideration for low EA assessment and screening. Abstract : Supplemental digital content is available in the text.